Prison life of Jefferson Davis : embracing details and incidents in his captivity, particulars concerning his health and habits, together with many conversations on topics of great public interest - Craven, John Joseph, 1822-1893 (Carleton, 1866)
This book examines Jefferson Davis's time in prison after the Civil War.